Cabazitaxel Versus Topotecan in Patients with Small-Cell Lung Cancer with Progressive Disease During or After First-Line Platinum-Based Chemotherapy. Issue 8 (August 2015) - Evans, Tracey L.; Cho, Byoung Chul; Udud, Katalin; Fischer, Juergen R.; Shepherd, Frances A.; Martinez, Pablo; Ramlau, Rodryg; Syrigos, Konstantinos N.; Shen, Liji; Chadjaa, Mustapha; Wolf, Martin
Abstract : Introduction: Patients with small-cell lung cancer (SCLC) typically respond well to initial chemotherapy. However, relapse invariably occurs, and topotecan, the only approved second-line treatment option, has limited efficacy. Taxanes have activity in SCLC, and cabazitaxel is a second-generation taxane with potential for enhanced activity in chemorefractory malignancies. Methods: Patients with SCLC who relapsed after initial platinum-based chemotherapy were randomly assigned to receive cabazitaxel 25 mg/m 2 every 21 days or topotecan 1.5 mg/m 2 on days 1–5 every 21 days. Two patient subgroups, defined by chemosensitive and chemo-resistant/refractory disease, were assessed in combination and separately. Results: The safety profile of cabazitaxel and topotecan was consistent with previous studies, and despite considerable toxicity in both arms, no new safety concerns were identified. Patients receiving cabazitaxel had inferior progression-free survival compared with topotecan (1.4 versus 3.0 months, respectively; two-sided p < 0.0001; hazard ratio = 2.17, 95% confidence interval = 1.563–3.010), and results were similar in both the chemosensitive and chemorefractory subgroups. No complete responses were observed in either arm, and no partial responses were observed in the cabazitaxel group. The partial response rate in the topotecan arm was 10%. Median overall survival was 5.2 months in the cabazitaxel arm and 6.8 months in the topotecan arm (two-sided p = 0.0125; hazard ratio = 1.57, 95% confidence interval = 1.10–2.25). Conclusion: Cabazitaxel, a next-generation taxane, had inferior efficacy when compared with standard-dose topotecan in the treatment of relapsed SCLC. Topotecan remains a suboptimal therapy, and continued efforts to develop improved second-line treatments are warranted.